Waste-to-BioEnergy pathway for waste activated sludge from food processing industries: An experiment on the valorization potential under CO₂ and N₂ atmospheres through microwave-induced pyrolysis - Guo, Ren Mong; Chong, William Woei Fong; Siti Aminah Mohd Nor; Ng, Jo-Han; Chong, Cheng Tung; Rubia Idris; Chiong, Meng Choung; Syieluing Wong; Bemgba Bevan Nyakuma (Elsevier, 2022)
Pyrolysis is a green and effective method for converting various waste streams into products with bio-energy potential. Waste activated sludge (WAS) from industries requires post-treatment before disposal and will cause serious pollution if not managed properly. Pyrolysis is a viable method for converting WAS into highervalue bio-products. This is the first study to use a lab-scaled microwave reactor to analyse WAS from a food processing and manufacturing company’s wastewater treatment plant. The goal is to compare bioproduct formation under various N2 and CO2 atmospheres in order to analyse the WAS waste-to-bioproduct transformation pathway. Result revealed that CO2 pyrolysis on WAS tends to: 1) increase water formation (~19 wt%), 2) produce biochar with higher energy density profit (~14%) and 3) generate gaseous products with a higher CO proportion (~50 vol%). WAS pyrolysis under N2 atmosphere showed 1) an overall better energy profit (<83.2 %), while producing 2) a higher gaseous yield (~32 wt%) with 3) higher H2 proportion (~29 vol%) and 4) biochar of larger surface area (22 m2 /g). Integrating CO2 as the pyrolysis medium utilises the excess CO2, potentially relieving the carbon burden on the environment